2013
DOI: 10.1097/maj.0b013e31828bdedf
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Type 2 Diabetes

Abstract: Type 2 diabetes mellitus (T2DM) has been described as a new epidemic. Approximately 285 million people worldwide suffer from diabetes, and this number is predicted to increase by about 50% by year 2030.This article will review oral health manifestations of diabetes, and discuss associations between periodontal disease and diabetes. Although there is a strong body of evidence that supports the relationship between oral health and T2DM, oral health awareness is lacking among patients with diabetes and other heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 38 publications
3
109
1
12
Order By: Relevance
“…Type 2 diabetes mellitus (T2DM) is the most common form of diabetes accounting for almost 80-90% of all diagnosed cases of diabetes [Leite et al 2013]. It is also becoming more prevalent among children, adolescents and younger adults [Chen et al 2012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 2 diabetes mellitus (T2DM) is the most common form of diabetes accounting for almost 80-90% of all diagnosed cases of diabetes [Leite et al 2013]. It is also becoming more prevalent among children, adolescents and younger adults [Chen et al 2012].…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming an epidemic of our time creating a major and challenging public health problem confronting every nation on the globe [Badran and Laher, 2012;Leite et al 2013]. According to the World Health Organization (WHO) fact sheet (2011), 347 million people worldwide are living with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…10 Diabetes mellitus is chronic disease leading to disturbed oral health status especially compromised periodontal health. 11,12,13 Before starting discussion and establishing the conclusion, it should be pointed out that only few studies have been carried out to demonstrate the role of Insulin therapy in type-1 diabetes mellitus on bone remodeling and orthodontic tooth movement. A study conducted on diabetic rats showed an increased orthodontic tooth movement and osteoclast count.…”
Section: Discussionmentioning
confidence: 99%
“…With so much information to review for a particular patient, few medical professionals recognize the impact that a raging dental abscess or the chronic inflammation of periodontal disease could have on a pregnant woman or diabetic patient [4]. Many care coordination teams include valuable interdisciplinary members, such as pharmacists, social workers, or nurse clinicians, but when it comes to the mouth, not much gets said (pun intended) or done.…”
mentioning
confidence: 99%